The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fnut.2020.609022
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Methyl-Donor Micronutrient Supplementation During Pregnancy Promotes Skeletal Muscle Differentiation and Maturity in Newborn and Weaning Pigs

Abstract: Adequate maternal methyl-donor micronutrient (MET) intake is an important determinant of the organ development and metabolic renovation of offspring. The mechanism involved in skeletal myogenesis and the effect of MET supplementation during pregnancy on the maternal body remain unclear. Thus, this study aimed to investigate the potential effect of methyl donor micronutrients (MET) on skeletal muscle development and metabolism in offspring using pig models. Forty-three Duroc × Erhualian gilts were assigned to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 55 publications
1
11
1
Order By: Relevance
“…In a previous study, we found no differences in reproductive performance of sows between CON and MET; however, we observed that the offspring of sows fed with the MET diet grew faster than control offspring, and maternal MET exposure can promote skeletal muscle differentiation and maturity and improve the skeletal muscle mass of weaning piglets (14). Previous research reports the intestinal tract of the monogastric animal plays a crucial role in nutrient digestion and absorption and maintains the barrier function against malignant pathogens and antigens (20).…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…In a previous study, we found no differences in reproductive performance of sows between CON and MET; however, we observed that the offspring of sows fed with the MET diet grew faster than control offspring, and maternal MET exposure can promote skeletal muscle differentiation and maturity and improve the skeletal muscle mass of weaning piglets (14). Previous research reports the intestinal tract of the monogastric animal plays a crucial role in nutrient digestion and absorption and maintains the barrier function against malignant pathogens and antigens (20).…”
Section: Discussioncontrasting
confidence: 52%
“… Effect of maternal methyl-donor micronutrient supplementation during gestation on birth weight and weaning weight of offspring piglets ( n = 21). No difference was observed for litter size of lactating sows between treatments [data not shown, see reference ( 14 )]. The litter of each sow was considered as the experimental unit to calculate the individual weight of piglets at birth and weanling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In pigs, studies are not as extensive; however, a similar effect of betaine on DNA methylation in piglets has been demonstrated [ 134 ]. Recently, He et al (2020) studied the effect of methyl donors, such as folate, choline, and methionine supplementation in pregnant sows, and the results showed an increase of proteins of one-carbon-unit metabolism in females and piglets, and skeletal muscle differentiation increase in piglets, probably regulated by epigenetic modifications [ 135 ]. However, since, in this study, the supplementation was performed with all the methyl group donors simultaneously, the effect of each of them in pigs remains to be discovered.…”
Section: Epigenetic Effect Of Diets In Pigsmentioning
confidence: 99%